Pemberdayaan Masyarakat dalam Revitalisasi Lingkungan Berkelanjutan melalui Pengelolaan Sampah Rumah Tangga - Heri Kiswanto; Khoirotun Nafillah; Ngatmin Ngatmin; Purwanto Purwanto; Lia Retian Asfirah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Household waste management in RW 03, Kelurahan Genuk, Ungaran Barat, is still carried out conventionally without sorting, causing environmental pollution, reduced air and soil quality, and limiting the potential utilization of waste. This community service program aims to increase residents' awareness, knowledge, and skills in household waste management through the establishment of RW 03 Waste Bank and the application of simple, appropriate technologies, such as composters, waste sorters, and recycling tables. A participatory approach was implemented through stages of coordination and socialization, followed by a needs analysis, training, and practice in making compost, ecoenzymes, and upcycling products, with continuous mentoring and evaluation. The results show the establishment of RW 03 Waste Bank, an increase in residents’ participation in waste management up to 70%, and regular use of appropriate technology facilities. This program offers tangible benefits, including enhanced environmental awareness, community independence in managing waste, and economic value from processed waste products, while also serving as a replicable model for community empowerment in other areas.